Workplace stress and burnout among university lecturers in Indonesia and Malaysia: A systematic review of stressors, outcomes, and protective factors - Mimi Haryani Hassim; Dian Puspitaningtyas Laksana; Rachmy Rosyida Rais; Ronal Surya Aditya (CV Rezki Media, 2025)
Background: Workplace stress and burnout have emerged as critical occupational health concerns among university lecturers, particularly amid increasing academic workloads, performance pressures, and organizational demands intensified during and after the COVID-19 pandemic. Despite growing empirical attention, evidence remains fragmented, especially within Southeast Asian higher education contexts. Objectives: This study aims to systematically review empirical research on workplace stress and burnout among university lecturers in Indonesia and Malaysia, with a focus on identifying key stressors, associated outcomes, and protective factors. Methods: A systematic literature review was conducted following the PRISMA 2020 guidelines. Peer-reviewed articles published in English were retrieved from the Scopus database using predefined search terms related to workplace stress, burnout, lecturers, and higher education in Indonesia and Malaysia. After screening and eligibility assessment, 19 studies published between 2004 and 2025 were included. Methodological quality was assessed using the Newcastle–Ottawa Scale, and findings were synthesized through qualitative narrative analysis due to study heterogeneity. Results: The review reveals that workplace stress and burnout are prevalent among university lecturers in both countries. Major stressors include excessive workload, role ambiguity, performance-based evaluation systems, work–life imbalance, and limited organizational support. These stressors are consistently associated with adverse outcomes such as emotional exhaustion, reduced job satisfaction, impaired performance, and increased turnover intention. Protective factors, including social support, supportive leadership, emotional intelligence, and workplace spirituality, were found to mitigate stress and burnout effects. Conclusions: Workplace stress and burnout among university lecturers in Indonesia and Malaysia are multifactorial and systemic issues embedded in contemporary academic work environments. Organizational- and policy-level interventions are essential to promote lecturer well-being and ensure sustainable academic careers.